DEVELOPMENT OF THE TOURISM BUSINESS IN BISHKEK AS A SECTOR OF THE ECONOMY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the fact that, despite Bishkek’s exceptionally advantageous economic and geographical location, its convenient transport interchange and location on the Great Silk Road crossing Eurasia, the tourism business is currently, unfortunately, not developing sufficiently, and a number of main reasons for this are considered. To eliminate this negative situation and develop the tourism business, the authors proposed to implement a number of measures, primarily aimed at developing the natural and recreational potential of the foothills and gorges south of the city. It was emphasized that for the comprehensive and effective implementation of the identified problems, it is necessary, first of all, to develop a “Strategy for the development of the tourism business of Bishkek.”
Keywords: Tourism, business, city, Manas, mountain, potential, strategy, virtual tourism, innovation, ethnography.